2020
DOI: 10.1097/mpg.0000000000003037
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID‐19 on Job Prospects and Educational Training for Pediatric Gastroenterology Fellows

Abstract: Objectives: The COVID-19 pandemic has significantly affected graduate medical education with redistribution of trainees, altered clinical care, and decreased research. For graduating trainees, there remains concern that financial stability of health systems will affect the availability of new positions and hiring practices. This survey aims to evaluate the pandemic's impact from pediatric gastroenterology fellows’ perspectives. Methods: An anonymous sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Nearly two-thirds of trainees who completed training in 2020 reported having had at least one post-training job offer rescinded, perhaps owing to decreased revenue and hiring freezes [ 15 , 24 , 25 ]. Although the impacts are not yet clear, a minority of trainees reported a negative impact of the pandemic on their ability to find a job.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly two-thirds of trainees who completed training in 2020 reported having had at least one post-training job offer rescinded, perhaps owing to decreased revenue and hiring freezes [ 15 , 24 , 25 ]. Although the impacts are not yet clear, a minority of trainees reported a negative impact of the pandemic on their ability to find a job.…”
Section: Discussionmentioning
confidence: 99%
“…With the reduction in endoscopic procedures, outpatient visits and hospital admissions, the opportunities for typical clinical training of fellows were diminished during the first several months of the pandemic 61 , 79 . A survey of program directors revealed that endoscopy and typical outpatient clinical experiences were drastically reduced, but fellows were included with the rapid adoption of telehealth for outpatient visits 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many fellows altered their research methodology or refocused on an alternative project. When fellows were surveyed, large proportions reported subjective negative impact on clinical (52%), research (46%) and procedural confidence (41%) 79 . A small but important proportion of fellows graduating in the summer of 2020 reported that their post-fellowship employment contracts were altered or rescinded due to hiring freezes attributed to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 2 This survey found a substantial influence of the early pandemic on job attainment with notably 5 graduating fellows reporting rescinded job offers and half of first- and second-year fellows reporting a high level of concern in finding a job. 2 The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition trainee survey in 2020 additionally demonstrated the impact in clinical practice, mental health, quality of care provided, and fellowship/trainee experience. 3 In all, these surveys have highlighted the initial effects of the COVID-19 pandemic; however, the presence of continued effects has been understudied.…”
Section: Introductionmentioning
confidence: 79%
“…The previous NASPGHAN 2020 fellows survey was reviewed and updated to target more pertinent concepts for NASPGHAN fellows in the evolving COVID-19 pandemic. 2 The final survey included 31 total questions. Compared to the 2020 survey, there were 11 questions that remained the same, 3 questions that had wording adjusted for clarity or updated year of survey, 7 questions that had additional answer choices to gather more information, and 10 new questions to further address our survey aims.…”
Section: Methodsmentioning
confidence: 99%